Relationship of Health-promoting Behaviors with Demographic and Pregnancy Characteristics in Overweight and Obese Pregnant Women who Refer to Comprehensive Health Centers in Bijar, Iran - Parivash Safaryan; Mansoureh Jamshidimanesh; Shima Haghani (Hamadan University of Medical Sciences, 2023)
Background and Objective: This study aimed to determine the relationship of health-promoting behaviors with demographic and pregnancy characteristics in overweight and obese pregnant women in Bijar, Iran. Materials and Methods: This cross-sectional study was conducted on 194 pregnant women who were selected from five comprehensive health centers in Bijar, Iran, in 2020, using the convenience sampling method. The data were collected via demographic and pregnancy characteristics form and Walker's health promotion lifestyle questionnaire. Following that, the independent t-test, one-way ANOVA, Pearson correlation coefficient, and multiple linear regression were used for data analysis. A P-value of 0.05 was considered statistically significant. Results: The health-promoting behaviors of pregnant women were explained under the influence of gestational age and the number of prenatal care. The results showed that obese and overweight pregnant women who had 7 to 8 prenatal cares had a higher and significant mean score of health promoting behaviors, compared to pregnant women who had 1 to 2 cares (β=5.30; Ρ=0.022). Moreover, pregnant women whose gestational age was more than 35 weeks obtained a higher and significant mean score of health-promoting behaviors than pregnant women with a gestational age of less than 25 weeks (β=7.54; Ρ=0.03). Conclusion: Using these findings, in addition to the number of pregnancy cares and age of pregnancy, it seems that there are other factors affecting health-promoting behaviors in pregnant women.